(untitled) (Research, Society and Development, 2022)
Introduction: Because it is a very common neoplasm worldwide, the treatment of breast cancer is always updated, aiming to increase the quality of life and aesthetic satisfaction of patients. Objective: To expose the developments in the surgical treatment of breast cancer, according to the world literature. Methodology: A literature review was carried out with the following thematic question: what are the current innovations in surgical treatments for breast cancer? The descriptors "breast cancer AND surgery" were searched in the following databases: SciELO, PubMED and LILACS. Inclusion criteria were articles published in the last 3 years, in Portuguese, English or Spanish, and that answered the guiding question. Commentaries and editorials, paid or incomplete articles, duplicates and studies that did not fit the theme were excluded. Results: a total of 5963 articles were obtained, reduced to a final sample of 12 articles after selection based on the inclusion and exclusion criteria. Oncoplastic surgery proved to be the most current practice for the treatment of breast cancer, along with sentinel lymph node biopsy and intraoperative radiation. The main benefits cited were improvement in the quality of life and in the patient’s self-esteem. Final Considerations: oncoplasty should be included in the oncologic surgeon’s training, so that he can offer the best treatment for his patients. In addition, methods for the diagnosis of early breast cancer should be encouraged and studied, so that the treatment and prognosis are favored.